Cartilage Stiffness Effect on Foot Biomechanics of Chinese Bound Foot: A Finite Element Analysis - Zhang, Yan; Awrejcewicz, Jan; Baker, Julien S.; Gu, Yaodong (Frontiers in Physiology, 2018)
The purpose of this study is to investigate the effect of cartilage stiffness on inner foot biomechanics of Chinese bound foot while balanced standing using finite element method. A three-dimensional FE model of bound foot involving 28 bones, 72 ligaments, 5 plantar fascia, cartilages, and encapsulated soft tissue was constructed and validated. To conduct the sensitivity analysis of cartilage stiffness, the incremental Young’s modulus of 1, 5, 10, and 15 MPa were assigned to the cartilage. 25% of the body weight was applied to the Achilles tendon to adjust the anterior- posterior displacement of center of pressure agreeable with the measured result. As the Young’s modulus of cartilage increased, the peak von Mises stress in the fifth metatarsal increased obviously, while that in the calcaneus remains unchanged. The plantar fascia experienced reduced total tension with stiffer cartilage. The cartilage stiffening also caused a general increase of contact pressure at mid- and forefoot joints. Cartilage stiffening due to foot binding gave rise to risks of foot pain and longitude arch damage. Knowledge of this study contributes to the understanding of bound foot biomechanical behavior and demonstrating the mechanism of long-term injury and function damage in terms of weight-bearing due to foot binding.